Equality of Opportunity: Theory and Evidence - Francisco H. G. Ferreira; Vito Peragine (Institute for the Study of Labor (IZA), 2015)
Building on earlier work by political philosophers, economists have recently sought to define a concept of equity that accommodates the fairness of reward to individual responsibility and effort, while allowing for the existence of some inequalities which are unfair and should be compensated. This paper commissioned as a chapter for the Oxford Handbook of Well Being and Public Policy provides a critical review of the economic literature on equality and inequality of opportunity. A simple 'canonical model' of equal opportunity is proposed, and used to explore the two fundamental concepts in this (relatively) new theory of social justice: the principles of compensation and reward. Ex-ante and ex-post versions of the compensation principle are presented, and the tensions between them are discussed. Different approaches to the measurement of inequality of opportunity and empirical applications are reviewed, and implications for the measurement of poverty and of the rate of economic development are discussed.
Keywords: D63; I32; 330; equality of opportunity; inequality of opportunity; compensation; reward